Residential Mobility Among Elementary School Students in Los Angeles County and Early School Experiences: Opportunities for Early Intervention to Prevent Absenteeism and Academic Failure - Green, Gabrielle; DeFosset, Amelia; Kuo, Tony (Frontiers in Psychology, 2019)
School connectedness is closely linked to academic success: students who are engaged at school have better attendance and academic performance, and are less likely to drop out. Residential mobility – having moved homes – can increase the risk of a negative academic trajectory (e.g., absenteeism and academic failure). Increasing housing instability in the United States due to rising housing costs, especially in urban areas, has made residential mobility a growing concern. While existing research has examined residential mobility among students and its connection to long-term consequences such as absenteeism and academic failure, less is known about how residential mobility relates to potential intermediate school experiences (e.g., school disconnectedness, low perceived academic ability, experiences with school violence and harassment) that contribute to a negative academic trajectory. This study examines associations between residential mobility in elementary school and school experiences in a large urban jurisdiction. Data were collected from a sample of public elementary school students in Los Angeles County (5th grade, n=5,620) via the California Healthy Kids Survey (2013-2014). Descriptive, chi-square, multiple logistic regression analyses, and predicted probabilities were performed to examine the relationships between past-year residential mobility and indicators of school connectedness and school-based relationships, perceived academic performance, and exposure to violence and harassment. More than a third (36.6%) of students in the analysis sample moved at least once in the past year. After adjusting for neighborhood and family factors, a higher number of past-year moves was significantly associated with poorer school experiences, including lower odds of school connectedness for high-movers (2+ moves) (adjusted odds ratio [AOR]=0.77; 95% confidence interval [CI]=0.68-0.86), as compared to non-movers. Movers had lower odds of perceived academic ability (1 move: AOR=0.72; CI=0.63-0.83; 2+ moves: AOR=0.55; CI=0.44-0.69), but higher odds of exposure to violence and harassment as a victim (1 move: AOR=1.26, CI=1.17-1.37; 2+ moves: AOR=1.34, CI=1.17-1.54), and as a perpetrator (1 move: AOR=1.21, CI=1.08-1.36; 2+ moves: AOR=1.54, CI=1.24-1.92). These results highlight the value of developing and implementing strategies that can identify and support students who move at young ages, to prevent student disengagement and promote attendance and academic success early in their life trajectory.